THE EFFECTIVENESS OF SHADOWING TECHNIQUE IN ENHANCING PRONUNCIATION SKILL OF EIGTH GRADE STUDENT AT SMP NEGERI 8 GORONTALO - Alief Bahasoan; Hanisah Hanafi; Irmawaty Umar (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study investigates the effectiveness of the shadowing technique in improving word-stress pronunciation of eighth-grade students at SMP Negeri 8 Gorontalo. Using a one-group pretest–posttest quantitative design, thirty-two students (class VIII-2) participated in six scaffolded shadowing sessions. Pronunciation performance on a 10-item word list was recorded and scored using the Speakometer application; pretest and posttest scores were subsequently analyzed with a paired-samples t-test. Results indicate a substantial improvement in mean scores from 37.65 (SD = 11.29) at pretest to 70.03 (SD = 11.90) at posttest, and the difference was statistically significant (paired t, p = .000), supporting the alternative hypothesis that shadowing significantly enhances word-stress accuracy. Classroom observations suggested that gains stemmed from improved stress placement, clearer vowel reduction in unstressed syllables, and greater prosodic automaticity following graded practice and peer/teacher feedback. While limitations include the single-group design, single-class sample, and short intervention window, findings suggest that teacher-guided shadowing combined with app-based feedback is a practical and effective method for addressing word-stress issues in EFL middle-school contexts. Implications for pedagogy and directions for controlled, larger-scale studies are discussed.